2018
DOI: 10.1088/2057-1976/aaa0b0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TiNi-based wire mesh implant for abdominal wall defect management

Abstract: Purpose. Synthetic meshes are now widely used for a repair of various tissue defects. Polypropylene meshes (PPMs), the type most frequently used for repair of abdominal wall defects, have some disadvantages, therefore the development of new mesh materials for reconstructive surgery is an important topic. A TiNibased alloy superelastic mesh implant has been compared with a PPM in the Wistar rat model. Experimental. A midline resection abdominal wall defect (2 cm×3 cm) was treated with a mesh implant (2.5 cm×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The reviewed literature stresses the importance of customized design in modern reconstructive surgery, which is also relevant for the KTNM. The positive interaction between the KTNM and surrounding tissues was previously studied in animal models [7,26], and it was also assessed clinically in 120 cancer patients, as reported in Refs. [10,27], where the survivability of KTNM placed in highly virulent media was highlighted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reviewed literature stresses the importance of customized design in modern reconstructive surgery, which is also relevant for the KTNM. The positive interaction between the KTNM and surrounding tissues was previously studied in animal models [7,26], and it was also assessed clinically in 120 cancer patients, as reported in Refs. [10,27], where the survivability of KTNM placed in highly virulent media was highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…Each KTNM is made of the TN-10 alloy superelastic filaments (60 µm in diameter), having a microporous, oxicarbonitride superficial layer [29,30]. The bio-mimic in vitro/vivo features of TiNi-based constructs have been reported to resemble the behavior of human body tissues [26,31]. The light mesh is double knitted by a process which interlinks each filament junction and provides for superelasticity in any direction, as indicated in [10].…”
Section: Methodsmentioning
confidence: 99%
“…Optomesh is one of commercially available macroporous surgical implants. It is a nonresorbable, monofilament mesh made of polypropylene . The mesh was cut into smaller rectangular pieces in two separate directions dictated by the polypropylene fibers weaving (crosswise and lengthwise).…”
Section: Methodsmentioning
confidence: 99%
“…Overlapping the margins by at least 5 cm, a knitted TiNi mesh was placed over the thoracoabdominal defect and secured in the standard fashion, with outer edges of the mesh folded circumferentially. The surgical mesh used was knitted of the superelastic TiNi-based alloy filament, 60 μm in diameter, with bioinert oxycarbonitride surface studied by Zaworonkow et al [ 4 ] and also reported by Anikeev et al [ 6 ]. The mesh was fixed with maximum tension around the perimeter, using a simple continuous suture technique with atraumatic 3-0 prolene suture.…”
Section: Case Reportmentioning
confidence: 99%
“…In the context of a reinforcing material, customized bioadaptive TiNi-based implants are quite promising. There have already been reports of the successful use of such an approach [ [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%